Phalaropus fulicarius (Phalaropodidae) - Brüten - Rüppell, Georg (IWF (Göttingen), 1968)
Brütendes Thorshühnchen in seinem Biotop. Niedersetzen zum Brüten, Wegfliegen und Rückkehr zum Nest, Ordnen der Eier, Putzen der Handschwingen, Schlafen. : The film shows a brooding male Phalaropus fulicarius. To be seen are brood movements, and the bird preening itself, and sleeping. Phalaropus fulicarius